The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1021/jm991131h
|View full text |Cite
|
Sign up to set email alerts
|

3-Aryl-[1,2,4]triazino[4,3-a]benzimidazol-4(10H)-ones:  Tricyclic Heteroaromatic Derivatives as a New Class of Benzodiazepine Receptor Ligands

Abstract: A series of 3-substituted [1,2,4]triazino[4,3-c]benzimidazoles V were prepared and tested at the central benzodiazepine receptor (BzR). These compounds were designed as rigid analogues of the previously described N-benzylindolylglyoxylylamide derivatives IV. The title compounds V showed an affinity which depended directly on the presence of the N(10)-H group and an aromatic ring at position 3. Some of them elicited a 2- or 3-fold higher affinity with respect to that of the indolylglyoxylylamide derivatives IV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…Moreover, these results unequivocally demonstrated that for TBI derivatives, N(10)-H represents one of the necessary groups for interaction with the receptor site, as previously hypothesized by us [11].…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Moreover, these results unequivocally demonstrated that for TBI derivatives, N(10)-H represents one of the necessary groups for interaction with the receptor site, as previously hypothesized by us [11].…”
Section: Resultssupporting
confidence: 83%
“…The structure of compound 18 was confirmed by comparing its physical and spectral data with those of the 10-methyl isomer 15 and previously described similar products [11]. Actually, in the 1 H-NMR 18…”
Section: Chemistrysupporting
confidence: 61%
See 2 more Smart Citations
“…It involves the synthesis of 2-chloro-1-(2-phenylethyl)benzimidazole 2 by alkylation of the commercially available 2-chlorobenzimidazole 1 with 2-bromoethylbenzene in the presence of sodium hydride. 38 Heating 2 with hydrazine hydrate at 180°C in a Pyrex capped tube yielded the 2-hydrazone derivative 3, that was allowed to react in refluxing ethanol with (fur-2-yl)oxoacetic acid for 2 h. In agreement with our previous findings, 31,39 the obtainment of the target tricyclic compound FTBI proceeded through the formation of the intermediate 2-(benzimidazol-2-ylhydrazono)-2-furyl acetic acid 4 which was separated by cooling of the reaction mixture. It was isolated by filtration and purified by suspension in hot methanol.…”
Section: à11supporting
confidence: 87%